Peran Kompetensi Guru dalam Meningkatkan Kolaborasi Pembelajaran Terhadap Pola Pendidikan Moral Generasi Z - Nakhma Ussolikhah; Ilman Nafi'a (PT. Pusmedia Group Indonesia, 2024)
The deviant behavior of Generation Z teenagers causes difficulties for teachers at school. the difficulty of overcoming the attitudes and delinquency of teenagers in the technological era is a challenge for teachers in the technological era. The aim of this research is to reduce adolescent deviant behavior and increase student understanding. Research methodology with a qualitative approach to case study design. The primary subject consists of 1 client and the secondary subject consists of 3 clients. Data analysis using triangulation techniques. The research results describe that the client initial X has deviant behavior involved in illegal drugs as a user and dealer. After treatment using the Korlberg approach, individual counseling lasted 5 sessions. Y as a client identifies brawls between students, dating. There was a change in behavior from X in the initial stage, X experienced a loss of self-identity, in the 2nd stage. Stage 4 X is realizing the wrong actions and desires by deciding to leave the punk community and bad habits. Stage 5 X takes action by avoiding making friends with punk groups and starting to focus on living a better life as a reseller, utilizing technology to earn income and focusing on a future career. Keywords: Teachers; Moral Education; Generation Z